# How do you solve by substitution: 3x-8y=-7 and -5x-6y=3?

##### 2 Answers

#### Explanation:

-5(x) - 6y = 3

-5((-7 + 8y)/3) - 6y = 3

(35)/3 + (40y)/3 - 6y = 3

35 + 40y -2y = 1

38y = -34

y = -34/38

x = (-7 + 8(-34/38))/3

x = -269/57

I will let you finish off

#### Explanation:

Given:

Consider

Add

Divide both sides by 3

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

Using

Put everything over 3 to make calculation more straight forward.

Multiply both sides by 3

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

I will let you finish off